Generation and cardiac differentiation of a human induced pluripotent stem cell line UALGi002-A from a female patient with Left-Ventricular Noncompaction Cardiomyopathy - Calado, Sofia (2021)
Left Ventricular Noncompaction Cardiomyopathy (LVNC) is characterized by abnormal number and prominence of trabeculations of the left ventricle of the heart. Although LVNC has been associated with mutations in several genes encoding for transcriptional regulators, ion channels, sarcomeric and mitochondrial proteins, approximately 60% of LVNC patients do not present these genetic alterations. Here, we describe an induced pluripotent stem cell (hiPSC) line (UALGi002-A) originated from a LVNC female patient (LVNC-hiPSC) who does not present any previously known mutations associated to LVNC. The LVNC-hiPSC exhibited full pluripotency and differentiation potential and retained a normal karyotype after reprogramming. Moreover, the LVNC-hiPSC differentiated into contracting cardiomyocytes. This cellular model will be useful to study the molecular, genetic and functional aspects of LVNC in vitro.